2018
DOI: 10.1007/s00439-018-1873-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of the mitochondrial genome reveals common heteroplasmic sites in NADH dehydrogenase genes

Abstract: Increasing evidence implicates mitochondrial dysfunction in aging and age-related conditions. But little is known about the molecular basis for this connection. A possible cause may be mutations in the mitochondrial DNA (mtDNA), which are often heteroplasmic-the joint presence of different alleles at a single locus in the same individual. However, the involvement of mtDNA heteroplasmy in aging and age-related conditions has not been investigated thoroughly. We deep-sequenced the complete mtDNA genomes of 356 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…2) 7,20,21 . As previously reported 22,23 , mutational spectrum indicated a high transition to transversion (Ti/Tv) ratio of 16.44 ( Supplementary Fig. 3).…”
Section: Resultssupporting
confidence: 83%
“…2) 7,20,21 . As previously reported 22,23 , mutational spectrum indicated a high transition to transversion (Ti/Tv) ratio of 16.44 ( Supplementary Fig. 3).…”
Section: Resultssupporting
confidence: 83%
“…This finding was unexpected, as previous studies have identified increasing MtHz with age. Sequencing of blood DNA from 356 individuals from the Framingham Heart Study found elevated MtHz at multiple positions across the genome with increasing age ( 34 ). Similarly, a study of 2077 Sardinians using leukocyte DNA also found increasing MtHz and copy number reduction with increasing age ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…NDUFV1, NDUFS1, NDUFA13, NDUFC2, and NDUFB5 are NADH-dehydrogenases of mitochondria (25). NADH-dehydrogenase is one of the most important enzyme of complex I (26). Results of KEGG pathway analysis reveal that these differentially proteins are involved in ribosome, ECM-receptor interaction, oxidative phosphorylation, pyruvate metabolism, glucagon signaling pathway, and fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%